CASES OF THROMBOTIC EVENTS IN FIBROUS-CAVERNOUS PULMONARY TUBERCULOSIS PATIENTS - A. A. Yatsenko; T. I. Petrenko; P. N. Filimonov (Туберкулез и болезни лёгких)
The article describes three cases of deep venous thrombosis in those suffering from fibrous cavernous pulmonary tuberculosis. The causes of thrombotic complications were analyzed. In all cases the patients had a central venous catheter installed. The state of thrombotic readiness associated with genetic causes as well was confirmed in two patients. Under follow-up by thrombodynamics testing, it was found out that the effective dose of low-molecular heparin was above the estimated dose prescribed according to the instructions. One case had a lethal outcome. Certain actions to be taken by anesthesiologists and emergency physicians are offered in order to minimize the risk of thrombotic complications in pulmonary tuberculosis patients in need of surgery and (or) a venous catheter.